Análise progressiva da deformação e temperatura na superfície radicular geradas durante tratamento endodôntico e reabilitação de caninos superiores - Amade, Euridsse Sulemane (2011)
In root filled teeth, the lake of knowledge about potential deleterious of temperature rise and amount of strain generated during endodontic treatment and posterior rehabilitation with different types of intra-radicular posts is common. The produced heat and strain is dissipated on dentin structure, periodontal ligament and alveolar bone. The aim of this in vitro study was to investigate the effects of endodontic treatment and different post systems rehabilitation on the strain and temperature rise in two different root dentin regions. For this experimental investigation, twenty one extracted human canines teeth were sectioned 17 mm from their apex and divided into three groups (n = 7): cast post-and-core, fiber glass post and prefabricated steel post. All teeth were prepared for strain-gage and temperature rise measurement, attaching two strain gages on distal and two thermocouples on mesial root surfaces 2 mm and 10 mm from the crown cervical region. The samples were fixed in a specific apparatus developed for this study and strain and temperature rise were recorded during the following procedures: (1) root canal preparation, (2) Final rinse and drying, (3) obturation process, (4) canal relief, (5) post-space preparation, (6) Post modeling, (7) post trying, and (8) Resin cement curing process (9) Resin cement light curing process. Data were analyzed by oneway to compare both study factors among different procedures and two-way analysis of variance to compare post systems and root region, followed by the Tukey s HSD test ( = 0.05). Obturation process resulted in significantly higher strain values on cervical root region and the post-space preparation on the apical root region. The temperature rise reached in post-space preparation procedure was the most dangerous alteration (4.0 14.9°C), exceeding the critical values (10°C) even with water irrigation. The apical deformation produced in post-space preparation was the highest of the entire rehabilitation process: 473.9, 438.1 and 313.0 μS for fiber glass post, cast post and core and prefabricated steel post respectively. The resin cement light-curing resulted in significantly higher temperature on cervical region for all groups. Within the limitations of this study the following conclusions could be drawn: most evaluated procedures produced low temperature rise and strain values on cervical and apical root surface region, except obturation process, canal relief, post-space preparation and resin cement light-curing phase. Prefabricated steel post, inserted actively, resulted in high strain during the post trying and post cementation. Post-space preparation is a critical procedure and cautions must be taken to improve damage to the surrounding tissues.